Problems Faced by Elderly According to Gender in Rural Areas of Chittoor District - Hemavathi, U.; Swaroopa Rani, B. (International Journal of Social Sciences and Management, 2016)
Ageing is natural process spanning the life period from conception through birth,infancy, childhood, adolescenceand old age. In India aged people faced mainly three type’s problems those are physical/Health problems, financial problems and Socio-psychological problems. The present study was undertaken to know the problems faced by elderly living in rural areas of Mannarupalli (village). The sample consists of sixty (60) Elderly. People (30) Male and (30) Female.The sample was selected in three categories 60-70, 70-80, 80 and above. Purposive random sampling technique was used to select the sample, I have used interview schedule developed koala reedy (1990) was used to collect the information the statistical analysis used for percentage and frequencies were calculated. Results revealed from the study were majority of the elderly were facing physical problems and psychological problems than social problems .where as men are facing more physical and economic problems than women. Women were facing more psychological problems than men. Regarding social problem both the men and women are facing equally. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 65-67